Landscape of the Tocantins-Araguaia Basin: challenges, dynamics, and future prospect for conservation. - Schmitz, Marcelo Henrique (2024)
Tropical deforestation and unsustainable policies are current challenges in the Tocantins-Araguaia River basin (TOAR), located in the heart of the Cerrado biome. In the first article, the dynamics of land use were analyzed over a period of 35 years (1985-2020). The results showed relevant anthropogenic changes driven by agricultural activities, resulting in major vegetation losses, especially in natural forests, savannas and pastures. During this period, there was an exponential growth in pastures and agriculture to the detriment of natural categories. Part of TOAR's stable areas corresponded to legally protected areas. Considering the challenges highlighted in the first article, in the second, future scenarios of land use and cover (2015-2045) were analyzed under three area demand scenarios: "Business-as-usual" (BAUS), "Conservation-based" (CONS) and "Production-based" (PROD). Analysis of future projections indicated the persistence of deforestation and fragmentation patterns, especially in the PROD scenario. The notable predicted loss in Natural Forest and Savanna, even in the conservation scenario, highlights the urgent need for proactive conservation efforts, stricter regulations, and enhanced environmental considerations in development plans. Considering the context explored and discussed in the articles presented, this study not only highlights the complexities of the past dynamics of land use in TOAR, but also points to the urgency of coordinated actions to ensure a sustainable future. The persistence of deforestation even in conservation-oriented scenarios raises questions about the effectiveness of current protection measures, emphasizing the need to re-evaluate and strengthen conservation strategies. The TOAR is at an ecological crossroads, requiring concrete and targeted efforts on the part of decision makers, researchers and the population to ensure its sustainable management and the preservation of its unique ecosystems, biodiversity and cultural heritage amidst increasing anthropogenic pressures.